SPICE model of drain induced barrier lowering in sub-10 nm junctionless cylindrical surrounding gate MOSFET - Hakkee Jung (International Journal of Electrical and Computer Engineering (IJECE), 2020)
We propose a SPICE Drain Induced Barrier Lowering (DIBL) model for sub-10 nm Junctionless Cylindrical Surrounding Gate (JLCSG) MOSFETs. The DIBL shows the proportionl relation to the -3 power of the channel length Lg and the 2 power of silicon thickness in MOSFET having a rectangular channel, but this relation cannot be used in cylindrical channel because of the difference in channel structure. The subthreshold currents, including the tunneling current from the WKB (Wentzel-Kramers-Brillouin) approximation as well as the diffusion-drift current, are used in the model. The constant current method is used to define the threshold voltage as the gate voltage at a constant current, (2πR/Lg)10-7 A for channel length and channel radius R. The central potential of the JLCSG MOSFET is determined by the Poisson equation. As a result, it can be seen that the DIBL of the JLCSG MOSFET is proportional to the –2.76 power of the channel length, to the 1.76 power of the channel radius, and linearly to the oxide film thickness. At this time, we observe that the SPICE parameter, the static feedback coefficient, has a value less than 1 1, and this model can be used to analyze the DIBL of the JLCSG MOSFET.